The Influence of Product Availability, Packaging, and Service Quality on Purchase Decision with Customer Satisfaction as a Moderating - Peong, Hersanius Kurnia; Budiman, Aristo Afrianto; Ciptosari, Fitri (AKSIOMA : Jurnal Manajemen, 2025)
This study examines the influence of product availability, packaging, and service quality on purchasing decisions, with consumer satisfaction as a moderating variable. The research was conducted at Zasgo Mart, Labuan Bajo. A quantitative method was employed, using a questionnaire completed by 150 Zasgo Mart consumers. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The results show that, collectively, the three independent variables significantly affect consumer satisfaction. Among these, service quality is identified as a key factor that management must prioritize. Furthermore, consumer satisfaction strengthens the relationship between packaging and service quality with purchasing decisions, but does not moderate the relationship between product availability and purchasing decisions.